MATN3 Gene Polymorphism Is Associated with Osteoarthritis in Chinese Han Population: A Community-Based Case-Control Study - Jiaao Gu; Jiesheng Rong; Fulin Guan; Liying Jiang; Shuqing Tao; Guofa Guan; Tianzun Tao (The Scientific World Journal)
Background. The matrilin, especially matrilin-3 (MATN3), are reported to play important roles in the pathophysiology of osteoarthritis (OA). To explore the relationship between MATN3 SNP6 (rs8176070) and primary OA, we conducted a community-based case-control study. Methods. A total of 732 community residents aged 40–84 years participated in the community-based study in Northeast China. After taking physical and radiographic examinations, 420 of the residents were diagnosed OA (216 women and 204 men). The other 312 individuals without any symptoms of osteoarthritis or signs in the radiographs (156 women and 156 men) were considered as healthy controls. After obtaining the DNA of case and control groups, genotypes of the MATN3 SNP6 were determined by polymerase chain reaction followed by restriction enzyme digestion. The numbers of patients with different OA subtypes were also calculated. Results. The distribution of genotypes and alleles of the MATN3 SNP6 between OA patients and controls was different significantly. The BB carrier tends to be associated with the increased osteoarthritis (P = 0.025, OR = 1.724, 95% CI = 1.071–2.77), especially the knee osteoarthritis (P = 0.021, OR = 2.402, 95% CI = 1.141–5.060) and lumber osteoarthritis (P = 0.020, OR = 1.880, 95% CI = 1.103–3.204). Bb carrier increased hand osteoarthritis risk (P = 0.002, OR = 5.380, 95% CI = 1.828–15.835). The B allele might have an effect on the increased knee osteoarthritis (P = 0.000, OR = 3.143, 95% CI = 2.283–4.328). Conclusion. These findings suggest that the MATN3 gene polymorphism might be associated with osteoarthritis in the Chinese Han population.